Peningkatan kesadaran kritis melawan berita palsu dan ujaran kebencian melalui literasi digital - Rahayu, Sri; Meirawan, Danny; Sukadi, Sukadi; Ghinaya, Zahra; Sabitri, Zenita (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Most villages in Indonesia, such as Bugel Village, are vulnerable to the spread of hate speech and fake news online. This fake news often contains elements of hate speech against specific groups, such as ethnicity, religion, race, or class (referred to as SARA), which can trigger division and conflict within society. Therefore, it is important for the community to have a critical awareness strengthened through digital literacy, so that they can counter hate speech and fake news. The community service activity carried out by the Universitas Pendidikan Indonesia in Bugel Village, Tasikmalaya District, aimed to enhance digital literacy among the community. This activity involved 30 participants from various social strata, including village heads and farmers, focusing on digital literacy education to identify and counter the spread of fake news and hate speech online. Lecture and demonstration methods were used, and participants underwent pretests and posttests to measure improvements in understanding and application of digital literacy. The results showed significant improvement; the average pretest score for understanding increased from 55.8 to 85.8, and for application, from 65 to 86.1 in the posttest. Participants' satisfaction with the training was quite high, averaging 4.09. This activity successfully demonstrated the importance of digital literacy in the community, especially in facing digital information challenges such as fake news and hate speech, and emphasized the need for ongoing efforts to develop digital literacy in the community.